Spinal myoclonus: report of four cases - Mattos,James Pitágoras de (1993)
Four cases of spinal myoclonus are described, three males and one female. The mean age was 51 years (28-75 years). The mean time between the onset of the myelopathy and the myoclonic jerks was 4.3 months (1-8 months). The involuntary movements were determined by trauma, Devic's disease, tuberculous myelopathy and tumor. Three patients had spastic paraplegia with bilateral myoclonus more evident on the right side. The fourth patient had a flaccid paraplegia with symmetrical jerks. The data suggest that different processes (trauma, demyelinating, infection and tumor) affecting the spinal cord may cause the same type of involuntary movements.